2005
DOI: 10.1080/08941930590905189
|View full text |Cite
|
Sign up to set email alerts
|

2-Arachidonoylglycerol Increases in Ischemia–Reperfusion Injury of the Rat Liver

Abstract: Several studies have implicated endocannabinoids in various forms of shock. However, the role of endocannabinoids in hepatic ischemia-reperfusion injury remains unclear. The purpose of this study was to evaluate the changes of two endocannabinoidsin hepatic ischemia-reperfusion injury: anandamide (ANA) and 2-arachidonoylglycerol (2-AG). Male Sprague-Dawley rats were divided into 2 groups: the short (15 min) ischemic group and the long (60 min)ischemic group in the segmental (70%) hepatic tissue. Blood levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…It is noteworthy that there are at least two reports of increases in anandamide levels with no change in 2-arachidonoylglycerol levels following ischemia (Berger et al 2004;Hansen et al 2001b). This is in sharp contrast to the findings in the hepatic ischemiareperfusion model (Kurabayashi et al 2005) or an experimental acute myocardial infarction model (Wagner et al 2001), in which anandamide and 2-arachidonoylglycerol levels increased concurrently. The ischemic injury-induced elevations in endocannabinoid content, together with evidence that activation of the CB 1 receptor resulted in reduced central nervous system (CNS) excitability, implies that the endocannabinoid system comprises an endogenous protective mechanism during CNS injury (Mechoulam 2002;Mechoulam et al 2002b).…”
Section: The Endocannabinoid System and Neuropathologiescontrasting
confidence: 54%
“…It is noteworthy that there are at least two reports of increases in anandamide levels with no change in 2-arachidonoylglycerol levels following ischemia (Berger et al 2004;Hansen et al 2001b). This is in sharp contrast to the findings in the hepatic ischemiareperfusion model (Kurabayashi et al 2005) or an experimental acute myocardial infarction model (Wagner et al 2001), in which anandamide and 2-arachidonoylglycerol levels increased concurrently. The ischemic injury-induced elevations in endocannabinoid content, together with evidence that activation of the CB 1 receptor resulted in reduced central nervous system (CNS) excitability, implies that the endocannabinoid system comprises an endogenous protective mechanism during CNS injury (Mechoulam 2002;Mechoulam et al 2002b).…”
Section: The Endocannabinoid System and Neuropathologiescontrasting
confidence: 54%
“…The role of CB 2 receptors in I/R injury is supported further by increased accumulation of CB 2 -positive macrophages derived from resident microglia and/or invading monocytes following cerebral I/R [48]. Several studies have reported increased endocannabinoid levels following cerebral [18,[49][50][51][52] and hepatic I/R injury [44,53]; however, the role of endocannabinoids in I/R injury remains to be a controversial issue requiring further clarification. One possibility is that endocannabinoids released during I/R may try to limit the hepatic injury by modulating the expression of adhesion molecules and the infiltration and activation of inflammatory cells (mononuclear and polymorpho-nuclear leukocytes are known to express CB 2 receptors [6,21]) by CB 2 -dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…CB 2 receptor mRNA was also detected in cirrhotic but not in normal liver tissue . Endocannabinoids are detectable in the liver or liver cells both in animals and humans at levels similar to those in the brain and play an important role under various physiological and pathophysiological conditions Kurabayashi et al, 2005;Osei-Hyiaman et al, 2005b) (see also section III.A.3. ).…”
Section: G Gastrointestinal and Liver Disordersmentioning
confidence: 99%